Female Breast Cancer Patients, Mastectomy-Related Quality of Life: Experience from Ethiopia. (9th April 2020) - Abebe, Engida; Demilie, Kassaw; Lemmu, Befekadu; Abebe, Kirubel
Abstract : Background . Mastectomy is the most common form of treatment for a developing-nation woman diagnosed with breast cancer. This can have huge effect on a women's quality of life. Objective . To assess mastectomy-related quality of life in female breast cancer patients. Materials and Methods . A facility-based cross-sectional descriptive study was conducted from February 1 st to July 30 th, 2018. A pretested structured data collection format was used to interview patients. The European Organization for Research and Treatment for Cancer Quality of Life Questionnaire-Core 30 (EORTC QLQ-C30) and Breast Cancer-Specific (EORTC QLQ-BR23) were used to evaluate quality of life, functional capacity, and symptom scales. Data was analyzed with SPSS version 23. Results . The mean age of the 86 patients was 43.2 years (SD ± 11.4 ) and ranged from 25 to 70 years. 54.7% (47) of patient's mastectomy was done on the right side. Based on EORTC QLQ-C30 global health status/QOL scale, the mean score was 48.3. On the evaluation of EORTC QLQ-BR23, future perspective about their health was low with a mean of 40.3 and their sexual functioning and enjoyment were significantly affected with mean scores of 85.3 and 71.2, respectively. Symptom scales were low with mean from 19.1 to 24.5. Majority (49, 57%) of respondents do not want to have breast reconstruction after mastectomy. Conclusion . Our breast cancer patients who underwent mastectomy performed poor in terms of quality of life as compared to international findings which demands attention in incorporating psychosocial aspects in the treatment plan.